Effectiveness of Auricular Acupressure for Maternity Blues - Probowati, Rovica; Astuti, Andriani Mei; Anasulfalah, Hakim; Wahyuni, Dini Tri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Postpartum blues refers to mood changes experienced in the first days after giving birth. This problem appears starting three days to four days after giving birth with several symptoms such as emotional instability, anxiety, fatigue, confusion, irritability and others. From this postpartum problem, the aim of this research is that by providing auricular acupressure nursing therapy to mothers who have signs of baby blues, it can prevent recurrent baby blues. Mothers with postpartum blues, postpartum depression can become a psychological problem in pregnant women if ignored. Although postpartum blues has no specific medical treatment, it must be monitored in connection with the occurrence of diagnostic criteria for postpartum depression. This type of research is quantitative with a one group pretest and posttest research design. The results of auricular acupressure given to the mother after giving birth can prevent subsequent baby blues after giving birth. Auricular acupressure is effective in reducing postnatal sadness and depression, reducing maternal fatigue, and improving mother-infant attachment in the short term after birth.